Knowledge Level of Respondents Regarding Important Aspects Covered under DAESI Programme in Rajasthan - Rakesh Kumar; R. K. Verma, A. K. Jhajharia, Rohtash Kumar (Indian Journal of Extension Education, 2022)
Diploma in Agricultural Extension Services for Input Dealers (DAESI) programme is a one year diploma programme started by National Institute of Agricultural Extension Management (MANAGE) to impart technical knowledge on agriculture to input dealers. The programme is being implemented by MANAGE through SAMETIs under overall guidance and supervision of respective state departments. State Institute of Agriculture Management (SIAM) is designated as state level implementing institute in Rajasthan. The present study was conducted in agro-climatic zone IIIa (Semi Arid Eastern Plain) and V (Humid South Eastern Plain) of Rajasthan in the year 2021-22. Total 320 respondents, 160 beneficiaries and 160 non-beneficiaries were selected. Almost two third (64.37%) of beneficiaries had medium level of knowledge regarding important aspects covered under DAESI programme whereas in case of non-beneficiaries (68.12%) of respondents had medium to high level of knowledge. The beneficiaries also found high in level of knowledge in all the selected aspects to measure the knowledge level under study.